PENTINGNYA SANITASI BAGI KESEHATAN LINGKUNGAN DI PERTANIAN - Aqilla, Aulia Ryza; Razaq, Abdul; Yuniarti, Elsa; Handayuni, Linda (Fakultas Pertanian, Universitas Janabadra, 2024)
Sanitation and environmental health play a crucial role in maintaining the sustainability of modern agriculture. This research presents a synthesis of recent findings exploring key aspects of sanitation in an agricultural context. Wise waste management, sustainable water use, control of plant and animal diseases, and the role of modern technology are the main highlights. Empirical studies highlight that waste management practices, including recycling and utilization of biogas technology, can significantly improve the health of agricultural soil and water. Wise use of water, through smart irrigation systems and water conservation, is a key solution to facing the challenges of increasing water availability. Organic approaches to controlling plant and animal diseases are a focus of research, with an emphasis on the use of biological agents to reduce dependence on chemical pesticides. Modern technologies, such as smart sensors and geographic information systems, are emerging as important tools in monitoring and improving agricultural sanitation. Meanwhile, challenges such as climate change and population pressure underscore the need for a holistic approach and innovation. This abstract summarizes important findings that support the importance of sanitation and environmental health in maintaining agricultural sustainability. In conclusion, environmental sanitation and health is not only an ethical responsibility, but also a strategic investment for a sustainable agricultural future. Key-words: Sanitation, environmental Health, Agriculture INTISARI Sanitasi dan kesehatan lingkungan memainkan peran krusial dalam menjaga keberlanjutan pertanian modern. Penelitian ini menyajikan sintesis temuan terbaru yang mengeksplorasi aspek-aspek kunci sanitasi dalam konteks pertanian. Manajemen limbah yang bijaksana, penggunaan air yang berkelanjutan, pengendalian penyakit tanaman dan hewan, serta peran teknologi modern menjadi sorotan utama. Studi empiris menyoroti bahwa praktek manajemen limbah, termasuk daur ulang dan pemanfaatan teknologi biogas, dapat secara signifikan meningkatkan kesehatan tanah dan air pertanian. Penggunaan air yang bijaksana, melalui sistem irigasi pintar dan konservasi air, menjadi solusi kunci untuk menghadapi tantangan ketersediaan air yang semakin meningkat. Pendekatan organik dalam pengendalian penyakit tanaman dan hewan menjadi fokus penelitian, dengan penekanan pada penggunaan agen biologis untuk mengurangi ketergantungan pada pestisida kimia. Teknologi modern, seperti sensor pintar dan sistem informasi geografis, muncul sebagai alat penting dalam memantau dan meningkatkan sanitasi pertanian. Sementara itu, tantangan seperti perubahan iklim dan tekanan populasi menggarisbawahi perlunya pendekatan holistik dan inovasi. Abstrak ini merangkum temuan-temuan penting yang mendukung pentingnya sanitasi dan kesehatan lingkungan dalam menjaga keberlanjutan pertanian. Kesimpulannya, sanitasi dan kesehatan lingkungan bukan hanya tanggung jawab etis, tetapi juga investasi strategis untuk masa depan pertanian yang berkelanjutan. Kata kunci: Sanitasi, Kesehatan Lingkungan, Pertanian